Prevalence and Determinants of Mental Health Challenges Among Healthcare Workers Providing PMTCT Services in Ogun State, Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Mental health challenges among healthcare workers have garnered significant attention globally due to their profound impact on workforce efficiency and quality of care delivery. Healthcare providers offering Prevention of Mother-to-Child Transmission (PMTCT) services face unique stressors, including high patient loads, stigma, and inadequate resources, which may predispose them to mental health issues.Objective: This study aimed to assess the prevalence and determinants of mental health challenges among healthcare workers providing PMTCT services, with a focus on the interplay of demographic, workplace, psychosocial, and organizational factors.Method of Analysis: A cross-sectional study design was employed, involving 200 healthcare workers across across selected facilities. Data were collected using a structured questionnaire, which included the General Health Questionnaire-12 (GHQ-12) to measure mental well-being and additional sections for demographic, workplace, psychosocial, and organizational factors. Descriptive statistics, chi-square tests, and logistic regression were used for data analysis, with significance set at p